DEKONTRUKSI MAKNA SIMBOLIK LOGO UNIVERSITAS ACEH: PERSPEKTIF SEMIOTIK FERDINAND DE SAUSURE - Nurjannah, Nurjannah; Zuhra, Intan (Jurnal Sains Riset, 2025)
This study aims to deconstruct the symbolic meanings embedded in the logos of the two leading private higher education institutions in Pidie Regency—Universitas Jabal Ghafur and STAI Al-Hilal—using Ferdinand de Saussure’s semiotic framework. A qualitative descriptive method was employed, focusing on the analysis of signifier and signified elements. Data were collected through visual documentation, symbolic observation, and literature review. The findings reveal that both institutional logos incorporate visual elements reflecting Islamic values, intellectualism, and local wisdom. The logo of Universitas Jabal Ghafur features traditional Acehnese floral motifs such as bungong campli, bungong tanjong, reuhai, and bungong awan, symbolizing knowledge, strength, and prosperity. Meanwhile, the logo of STAI Al-Hilal Sigli presents a crescent moon and a book, representing religiosity and scholarly pursuit. The analysis shows that the relationship between signifier and signified is dynamic and contextual. These symbols serve as representations of institutional identity and philosophy, which are not fixed but open to various socio-cultural interpretations.Keywords: Semiotics, University Logos, Ferdinand de Saussure, Visual Identity